Enhanced Light Utilization in Semitransparent Organic Photovoltaics Using an Optical Outcoupling Architecture. Issue 40 (16th August 2019) - Li, Yongxi; Ji, Chengang; Qu, Yue; Huang, Xinjing; Hou, Shaocong; Li, Chang‐Zhi; Liao, Liang‐Sheng; Guo, L. Jay; Forrest, Stephen R.
Abstract: Building‐integrated photovoltaics employing transparent photovoltaic cells on window panes provide an opportunity to convert solar energy to electricity rather than generating waste heat. Semitransparent organic photovoltaic cells (ST‐OPVs) that utilize a nonfullerene acceptor‐based near‐infrared (NIR) absorbing ternary cell combined with a thin, semitransparent, high conductivity Cu‐Ag alloy electrode are demonstrated. A combination of optical outcoupling and antireflection coatings leads to enhanced visible transmission, while reflecting the NIR back into the cell where it is absorbed. This combination of coatings results in doubling of the light utilization efficiency ( LUE ), which is equal to the product of the power conversion efficiency ( PCE ) and the average photopic transparency, compared with a conventional semitransparent cell lacking these coatings. A maximum LUE = 3.56 ± 0.11% is achieved for an ST‐OPV with a PCE = 8.0 ± 0.2% at 1 sun, reference AM1.5G spectrum. Moreover, neutral colored ST‐OPVs are also demonstrated, with LUE = 2.56 ± 0.2%, along with Commission Internationale d'Eclairage chromaticity coordinates of CIE = (0.337, 0.349) and a color rendering index of CRI = 87. Abstract : An efficient and neutral colored semitransparent organic photovoltaic cell (ST‐OPV) is realized by utilizing a near‐infrared (NIR) absorbing ternary cell combined with a thin, semitransparent, high‐conductivity Cu–Ag alloy electrode. A combination of optical outcoupling and antireflection coatings leads to enhanced visible transmission, while reflecting the NIR back into the cell where it is absorbed.